Hospital-family collaborative DTT intervention to reduce the parenting stress through improving core symptoms and family functioning in children with autism spectrum disorder: a randomized controlled trial - Dai, Mengqin; Li, Juan; Chen, Xiaohong; Chen, Lian; Tang, Xiaocui; Yu, Haixia; Qiu, Yun; Yang, Yuwei (Frontiers in Pediatrics, 2025)
IntroductionAutism spectrum disorders (ASD) have emerged as a globally recognized public health concern. Currently, discrete trial teaching (DTT) is an effective intervention approach for ASD rehabilitation in hospitals. However, family-based interventions often yield limited outcomes. This study aims to develop a hospital-family collaborative DTT program guided by King's goal attainment theory, to support parents in delivering continuous and effective intervention within home environments.MethodThis single-blind randomized controlled study included 84 children with ASD aged 1 to 6 years. Participants were stratified by gender and age and randomly assigned to either the experimental group (n = 42) or the control group (n = 42) using a random number table. The experimental group received a hospital-family collaborative DTT program, consisting of one month of hospital intervention followed by three months of family-based intervention, while the control group received standard DTT rehabilitation. Outcomes were assessed using the Gesell Developmental Schedules (GESELL), Parenting Stress Index-Short Form (PSI-SF), Family Assessment Device (FAD), along with DTT theoretical and skill evaluations.ResultsExcept that the PSI scores were unaffected by the intervention method, the GESELL, PSI, FAD, theoretical, and skill scores were significantly influenced by both intervention time (F = 37.70–896.12, all P < 0.001), intervention method (F = 37.70–896.12, all P < 0.001), and their interaction (F = 5.83–75.27, all P < 0.01). Partial correlation analysis revealed that improvements in parenting stress were initially linked to changes in “adaptive” items on the GESELL and FAD scales during the hospital intervention phase (Δ FAD. affective reaction: rpartial = 0.225, P = 0.043; Δ GESELL. adaptation behavior: rpartial = −0.290, P = 0.009; Δ parental knowledge: rpartial = −0.432, P < 0.001), followed by improvements in “behavioral” items during the family-based intervention phase (ΔFAD. problem-solving: rpartial = 0.433, P < 0.001; ΔGESELL. gross motor behavior: rpartial = −0.292, P = 0.010; ΔGESELL. fine motor behavior: rpartial = −0.309, P = 0.012; ΔGESELL. personal-social behavior: rpartial = −0.327, P = 0.001). For all participants, extremely high levels of parenting stress were independently associated with FAD disorders (particularly in problem-solving, affective responsiveness, and affective involvement), child factors (including male, language disorder, and attention-deficit/hyperactivity disorder), caregiver factors (including male, lower education level, and unversed DTT skills), as well as conventional DTT programs and shorter intervention durations (all P < 0.05).DiscussionOur hospital-family collaborative DTT program significantly improved children's ASD symptoms, family function, and parenting stress, demonstrating the value of ongoing family-based DTT intervention. The improvements in children's symptoms and family function showed a time-dependent shift from adaptive to behavioral changes, which were linked to lower parental stress.